2018
DOI: 10.3390/w10010040
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Evaluation of Two High-Resolution Satellite-Based Rainfall Products: TRMM 3B42V7 and CMORPH in Shanghai

Abstract: Satellite-based rainfall products have extensive applications in global change studies, but they are known to contain deviations that require comprehensive verification at different scales. In this paper, we evaluated the accuracies of two high-resolution satellite-based rainfall products: the Tropical Rainfall Measurement Mission (TRMM) rainfall product 3B42V7 and the Climate Prediction Center morphing (CMORPH) technique from January 2010 to December 2011 in Shanghai, by using categorical metrics (Probability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 51 publications
8
22
0
Order By: Relevance
“…Due to the small changes in value at the thresholds used, very slight trends are observed in the indicators; however, the trends of POD and CSI agree with those found by Alijanian et al and Jiang et al [1,6], where an increase in the threshold value results in a decrease in the detection capacity. The CMORPH-CRT product presented a better performance in the detection capacity at the level of…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Due to the small changes in value at the thresholds used, very slight trends are observed in the indicators; however, the trends of POD and CSI agree with those found by Alijanian et al and Jiang et al [1,6], where an increase in the threshold value results in a decrease in the detection capacity. The CMORPH-CRT product presented a better performance in the detection capacity at the level of…”
Section: Discussionsupporting
confidence: 86%
“…The evaluation of the CMORPH precipitation was carried out through two approaches: (1) analysis of the capacity to detect precipitation; and (2) quantification of the accuracy or discrepancy between the CMORPH estimates and the precipitation data of the rain gauges of the weather stations [6,7,14]. For the first approach, precipitation data were considered categorical events and four indicators were used: probability of detection (POD), false alarm rate (FAR), critical success rate (CSI), and frequency bias index (FBI).…”
Section: Evaluation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few years, numerous studies have been carried out to validate the TRMM precipitation product in different regions [15][16][17][18][19][20]. Tong et al evaluated four widely used global high-resolution satellite precipitation products against gauge streamflow observations over the Tibetan Plateau [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, CMORPH satellite data, which are often used to evaluate model rainfall performance, underestimated the precipitation, particularly near the coast. Previous studies have reported that CMORPH 30 products substantially underestimated heavy rainfall (Jiang et al, 2018;Qin et al, 2014) and cold season rainfall (Xie et al, Atmos. Chem.…”
mentioning
confidence: 97%